The Impact of Smoking on Inflammatory Bowel Disease: A Literature Review - Grabowski, Krzysztof; Mioduszewska, Joanna; Rot, Paweł; Poniewozik, Piotr; Dziuba, Natalia; Sim, Aleksandra; Pernal, Maja; Roguska, Zofia; Zuzak, Andrzej Paweł; Poniewozik, Paweł (Quality in Sport, 2026)
Background. Inflammatory bowel disease (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), is a chronic immune-mediated condition with a rapidly rising global prevalence. While genetic factors are significant, environmental modifiers—specifically tobacco use—play a critical role in disease onset and progression. Background. Smoking cigarettes is a highly prevalent habit worldwide that has a massive impact on the human immune system, significantly influencing the onset and progression of various inflammatory conditions, including inflammatory bowel disease. Background. Cigarette smoking is one of the most common environmental exposures globally, significantly affecting the gut immune system and serving as a major modifying factor in chronic conditions such as inflammatory bowel disease. Aim. This literature review aims to synthesize current evidence regarding the impact of smoking on the development and clinical trajectory of CD and UC. Methodology. A comprehensive review was conducted using the PubMed and Google Scholar databases, focusing on peer-reviewed literature and consensus guidelines published between 2021 and 2026. Results. The literature confirms that smoking significantly increases the risk and severity of CD. In contrast, observational data traditionally suggest a protective effect of current smoking on UC onset, a phenomenon termed the "smoking paradox". However, recent genetic investigations using Mendelian randomization challenge the causality of this protection, suggesting it may stem from residual confounding. Conclusions. Despite the observational paradox in UC, the systemic harms and treatment interference associated with tobacco use necessitate universal cessation strategies. This review provides a clinical roadmap for managing smoking status in the modern era of IBD care.